Leadership through trust : leveraging performance and spanning cultural boundaries - Gordon, Gus (Palgrave Macmillan, 2017)
This book proposes that the key ingredient to effective leadership is trust and that leaders must earn the trust of their colleagues to be successful. The author uses his experience as a CEO in Mexico, a low trust society, as the basis of his model of trust leadership, which incorporates empathy and servant leadership principles. This book bridges the gap of abstract leadership concepts to practical application and implementation of leadership principles. Scholars can learn from the first-hand experience of the author as CEO while leaders can become more effective by grasping the theoretical underpinnings of leadership that the author offers.
Keywords: Leadership.; Trust.; Success in business.; elektronické knihy; electronic books